Evaluation of the usage of Google Classroom in Learning in Iraq: Evaluasi Penggunaan Google Classroom dalam Pembelajaran di Irak - Hasan, Hind Salah (Universitas Muhammadiyah Sidoarjo, 2025)
This study evaluates the adoption of Google Classroom in Iraq, focusing on its accessibility, usability, and impact on learning outcomes. Surveys and interviews were conducted with 500 students and 200 teachers, analyzed using SPSS and thematic analysis. Findings indicate that Google Classroom improves learning efficiency and engagement but faces infrastructural, technical, and cultural challenges. The study recommends prioritizing teacher training, digital literacy programs, and equitable access to technology for wider adoption.